Durvalumab after sequential chemoradiotherapy in stage III, unresectable NSCLC: the phase 2 PACIFIC-6 trial - Garassino, Marina; Mazieres, Julien; Reck, Martin; Chouaid, Christos; Bischoff, Helge; Reinmuth, Niels; Cove-Smith, Laura; Mansy, Talal; Cortinovis, Diego; Migliorino, Maria R.; Delmonte, Angelo; Sánchez, José Garcia; et al. (Journal of thoracic oncology, 2022)
On the basis of the findings of the phase 3 PACIFIC trial (NCT02125461), durvalumab is standard of care for patients with stage III, unresectable NSCLC and no disease progression after concurrent chemoradiotherapy (cCRT). Many patients are considered unsuitable for cCRT owing to concerns with tolerability. The phase 2 PACIFIC-6 trial (NCT03693300) evaluates the safety and tolerability of durvalumab after sequential CRT (sCRT).